Effects of chronic stress on cognitive function – From neurobiology to intervention - Milena Girotti; Sarah E. Bulin; Flavia R. Carreno (Neurobiology of Stress)
Exposure to chronic stress contributes considerably to the development of cognitive impairments in psychiatric disorders such as depression, generalized anxiety disorder (GAD), obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and addictive behavior. Unfortunately, unlike mood-related symptoms, cognitive impairments are not effectively treated by available therapies, a situation in part resulting from a still incomplete knowledge of the neurobiological substrates that underly cognitive domains and the difficulty in generating interventions that are both efficacious and safe.In this review, we will present an overview of the cognitive domains affected by stress with a specific focus on cognitive flexibility, behavioral inhibition, and working memory. We will then consider the effects of stress on neuronal correlates of cognitive function and the factors which may modulate the interaction of stress and cognition. Finally, we will discuss intervention strategies for treatment of stress-related disorders and gaps in knowledge with emerging new treatments under development.Understanding how cognitive impairment occurs during exposure to chronic stress is crucial to make progress towards the development of new and effective therapeutic approaches.